Hetty Feather - Wilson, Jacqueline; Sharratt, Nick (Yearling London, 2010)
It's London, 1876 and Hetty Feather is just a tiny baby when her mother leaves her at the Foundling Hospital. The Hospital cares for abandoned children - but Hetty must first live with a foster family until she is big enough to go to school. Life in the countryside is hard but with her 'brothers' Jem and Gideon, she helps in the fields and plays imaginary games. Together they sneak off to visit the travelling circus and Hetty is mesmerised by the show, especially Madame Adeline and her performing horses. But Hetty's happiness is threatened once more when she is returned to the Foundling Hospital. The new life of awful uniforms and terrible food is a struggle for her. But now she has the chance to find her real mother